Covid-19: Contributions from Psychopharmacology - Bauer, Michael; Juckel, Georg (Pharmacopsychiatry, 2022)
The COVID-19 pandemic is causing a major burden on personal health, healthcare systems and the global economy. For the last two years the COVID-19 pandemic has dramatically changed our lives in many personal and professional areas. For millions of us, due to infection rates, but also to protection measures such as lockdowns the corona pandemic has significantly changed the way we work, how we live, and how we interact with technology. In addition to the development of effective vaccines, anti-viral and anti-inflammation strategies are of eminent importance to treat people with acute infection or at least prevent serious negative outcomes. In contrast to the fast development of several effective vaccines that were remarkably available already after one year of the pandemic, novel effective anti-viral compounds are still in development. The only currently used effective medications against severe SARS-CoV-2 virus infection are corticosteroids 1.